Peningkatan Aktivitas Belajar Siswa melalui Pembelajaran Berbasis Bermain di TKIT Astyka Nailah Bekasi - Ahmad Syukron; SitiRahmah Shafrina (Prodi PIAUD IAI Pangeran Dharma Kusuma Indramayu, 2026)
This study aims to examine the enhancement of student learning activities at TKIT Astyka Nailah Bekasi through play-based learning, integrated with Islamic values. The research method used is descriptive qualitative, with data collection techniques including interviews, observations, and documentation on a TK B group consisting of 14 students. The results of the study indicate that the teacher's performance in planning, implementation, classroom management, and learning evaluation has a significant impact on improving student learning activities in visual, oral, motor, mental, and emotional aspects. A varied play-based approach and the use of innovative learning media have successfully created a conducive and enjoyable learning environment, thereby enhancing students' motivation and participation. The implications of these findings reinforce the importance of the teacher's role as a facilitator in Islamic-based early childhood education and provide practical contributions to the development of effective and holistic learning strategies in similar educational institutions.